Strengthening Energy Security in Uruguay - World Bank (Washington, DC, 2014)
The Uruguayan energy sector is at the crossroads. As in the case of many other countries, high oil prices in the international market are taking their toll on an economy which imports all of its oil and oil products. Uruguay has also depended, to a large extent, on import of electricity from Argentina to complement its supplies. Trade in electricity and natural gas collapsed during the economic recession of 2001-02 and Argentina's crisis in the same period, which, together with the rise of oil prices, have brought to the fore questions of energy security (that is, ensuring sufficient, reliable and cost-effective supply of national energy demand) and the cost/risk trade-offs involved in depending on foreign suppliers. The Uruguayan government has rightly perceived this to be a fundamental economic issue and sought to put together a strategy for addressing it.